2018
DOI: 10.1101/288159
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamic temperature-sensitive A-to-I RNA editing in the brain of a heterothermic mammal during hibernation

Abstract: RNA editing diversifies genomically encoded information to expand the complexity of the transcriptome. In ectothermic organisms, including Drosophila and Cephalopoda , where body temperature mirrors ambient temperature, decreases in environmental temperature lead to increases in A-to-I RNA editing and cause amino acid recoding events that are thought to be adaptive responses to temperature fluctuations. In contrast, endothermic mammals, including humans and mice, typically maintain a constant body temperature … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…In addition, several studies have shown that RNA editing reacts to various abiotic stresses, such as temperature, salt, etc. (Rieder et al 2015;Rodrigues et al 2017a;Riemondy et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several studies have shown that RNA editing reacts to various abiotic stresses, such as temperature, salt, etc. (Rieder et al 2015;Rodrigues et al 2017a;Riemondy et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, more and more RNA editing events were con rmed. To date, RNA editing has been found in primitive eukaryotes, vertebrates, plants, fungi and viruses (Palladino et al, 2000;Bahn et al, 2012;Alon et al, 2015;Guo et al, 2015;Riemondy et al, 2018;Zaidan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, our group has assembled and published the genome sequence of the Himalayan marmot (Marmota himalayana) and resequenced the whole genomes of another four marmots, including Mongolia marmot (Marmota sibirica), Gray marmot (Marmota baibacina), Long-tailed marmot (Marmota caudata) and Yellow-bellied marmot in 2019 [10]. Particularly, RNA-seq or microarray data from a broad range of mammal hibernators and plague hosts provide novel insight into understanding the special biological features of marmots, especially the molecular mechanism of hibernation [10][11][12][13][14][15][16]. However, there is no available database to save, exploit, analyze and distribute these largescale datasets.…”
Section: Introductionmentioning
confidence: 99%